2009
DOI: 10.1002/bit.22352
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lactic acid on cell proliferation and free radical‐induced cell death in monolayer cultures of neural precursor cells

Abstract: Biomaterials prepared from polyesters of lactic acid and glycolic acid, or a mixture of the two, degrade in the presence of water into the naturally occurring metabolites, lactic acid and glycolic acid. While the lactic acid degradation product that is released from biomaterials is well-tolerated by the body, lactic acid can influence the metabolic function of cells; it can serve as an energy substrate for cells, and has been shown to have antioxidant properties. Neural precursor cells, a cell population of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 33 publications
0
67
0
4
Order By: Relevance
“…[4][5][6][7][8]). Although PLA has been approved for these applications [4,9], several studies have also shown that contact of some of the PLA based products with human body is associated with biocompatibility problems including inducing nodules and foreign-body granulomas [10] and post-implantation inflammation [11].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8]). Although PLA has been approved for these applications [4,9], several studies have also shown that contact of some of the PLA based products with human body is associated with biocompatibility problems including inducing nodules and foreign-body granulomas [10] and post-implantation inflammation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the initial neuronal loss, PEG hydrogels enrich the initial cell population for NPCs and maintain higher NPC percentages throughout the culture period relative to monolayers. The increased nestin levels in PEG hydrogels were similar to those observed in neurosphere culture, suggesting that any potentially mitogenic factors within the PEG hydrogel environment itself, such as reactive oxygen species 51 or lactic acid degradation products, 47 do not substantially contribute to nestin maintenance. It was also determined that aggregated growth is insufficient for increased nestin expression given the decreased nestin observed in agarose cultures.…”
Section: Dapt Supplementationmentioning
confidence: 55%
“…While the mechanism of free-radical damage was not explored, a previous study proposed that Igacure 2959-generated free radicals may cause direct peroxidation of plasma membrane lipids. 47,48 Neurons may be particularly susceptible to free-radical damage given their lipid rich cellular membranes. 49 While maximizing the number of neurons present in PEG hydrogel culture is a priority for neuronal replacement therapies, efforts to rescue the fixed number of dissociated neurons may not be the most efficient approach to increase neuronal yields.…”
Section: Dapt Supplementationmentioning
confidence: 99%
“…Degradation can also confer advantages such as beneficial degradation products or controlled release of encapsulated molecules [Lampe et al, 2010a;Murphy et al, 2014;van Lith et al, 2014]. Polylactic acid, for instance, hydrolytically degrades releasing lactic acid, a normal metabolic product of glycolysis that may be beneficial to radical scavenging and cell protection [Lampe et al, 2009]. Controlled release, often through controlled degradation by combining polylactic acid with the faster degrading polyglycolic acid to form poly(lactic-co-glycolic acid) [PLGA], is also ideal because engineers can design materials which release molecules at a predetermined rate useful for cell survival or differentiation [Bible et al, 2009;Soderquist et al, 2010;Murphy et al, 2014].…”
Section: Polyestersmentioning
confidence: 99%